IMPROVING SPEED AND SPEED ENDURANCE IN SHORT-DISTANCE TRACK ATHLETES - Ruzmetov, Furqat (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This article analyzes approaches to improving speed and speed endurance in short-distance track athletes. The study evaluates training strategies that enhance sprint efficiency and competitive performance. The results support the effectiveness of targeted speed-endurance training. The study also explores the physiological and biomechanical factors influencing sprint performance, including muscle fiber composition, reaction time, stride length, and frequency. Special attention is given to the role of anaerobic energy systems and their development through high-intensity interval training. Furthermore, the article examines the importance of individualized training programs, proper load distribution, and recovery strategies in preventing fatigue and injuries. It highlights the effectiveness of combining technical drills, resistance training, and plyometric exercises to optimize speed and speed endurance. The paper concludes that a comprehensive and scientifically grounded training approach significantly enhances athletic performance in short-distance track events, contributing to improved results in competitive settings.